Crop residue and residue management effects on Armadillidium vulgare (Isopoda: Armadillidiidae) populations and soybean stand densities - Johnson, Wendy Ann; Alfaress, S.; Whitworth, R. Jeffery; McCornack, Brian P. (My University, 2012)
In general, Armadillidium vulgare (Latreille) are considered nonpests of soybean [Glycine max (L.) Merrill], but changes in soil conservation practices have shifted the pest status of this organism from an opportunistic to a perennial, early-season pest in parts of central Kansas. As a result, soybean producers that rotate with corn (Zea mays L.) under conservation tillage practices have resorted to removing excess corn residue by using controlled burns. In a 2-yr field study (2009-2010), we demonstrated that residue removal in burned compared with unburned plots (measured as previous crop residue weights) had minimal impact on numbers of live and dead A. vulgare, soybean seedling emergence, and isopod feeding damage over time. Specifically, removal of residue by burning did not result in higher emergence rates for soybean stands or less feeding damage by A. vulgare. In a separate study, we found that number of live A. vulgare and residue weights had no consistent relationship with seedling emergence or feeding damage. Furthermore, seedling emergence was not impacted by higher numbers of A. vulgare in unburned plots, indicating that emergence in this study may have been influenced by factors other than A. vulgare densities. These studies demonstrate that removing residue through controlled burning did not impact seedling emergence in presence of A. vulgare and that residue and feeding damage to seedlings did not consistently relate to A. vulgare densities. Other factors that may have influenced a relationship between residue and live isopod numbers, such as variable moisture levels, are discussed.
Citation: Johnson, W., Alfaress, S., Whitworth, J., & McCornack, B. (2012). Crop Residue and Residue Management Effects on Armadillidium vulgare (Isopoda: Armadillidiidae) Populations and Soybean Stand Densities. Journal of Economic Entomology, 105(5), 1629–1639. https://doi.org/10.1603/EC12040
Keywords: Soybean; Glycine max; Isopod; Armadillidium vulgare; Residue management